If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(-4x + -2) = 11 Reorder the terms: 3x + 2(-2 + -4x) = 11 3x + (-2 * 2 + -4x * 2) = 11 3x + (-4 + -8x) = 11 Reorder the terms: -4 + 3x + -8x = 11 Combine like terms: 3x + -8x = -5x -4 + -5x = 11 Solving -4 + -5x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -5x = 11 + 4 Combine like terms: -4 + 4 = 0 0 + -5x = 11 + 4 -5x = 11 + 4 Combine like terms: 11 + 4 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| -2(b-8)=-18 | | 4e^2x-2x=0 | | -4(8+5x)=20 | | 16-g=11 | | 4,5=x-13/-2 | | 15+2.50+5t=352.50 | | 272=16n | | 18/r2 | | 2-2y=14 | | c=10-4s | | 11x-17y=2 | | Log[5](2x+3)=2 | | 8(y)=2y+7 | | 36-n=2000 | | -(9y-14)=-15+29 | | x(2x-8)=-12 | | 19=-7(4k-9) | | 5(f+4)+9=-15 | | -7+4h=41 | | a+2=5+4a | | -9x-14=-15+29 | | -0.75n+7=25 | | 2+2x=4(2x+2)-7(x-1) | | 0.3(20X-30)=10 | | (3-2i)(7+6i)=0 | | 2(n-9)+8=-19 | | 20=-8a+9a | | 6y-8=9y+19 | | Ln(11x-3)=1.44567 | | 4x=x+17 | | 4/9x3/7x7/8 | | 8(2-z)+2(5z-4+a)= |